Personal Growth Initiative in Students in The Post-Pandemic Transition: Optimism, Internal Locus of Control, and General Self-Efficacy - Ria Wardani; Jacqueline Mariae Tjandraningtyas (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Personal Growth Initiative (PGI) refers to the change process done on purpose and reflects how a person changes and develops himself throughout his life span. University students, who are in the phase of emerging adulthood, will face many demanding and challenging events, so this is inevitably an opportunity for them to develop their potential to become fully functioning people. Various factors can encourage personal growth, namely optimism, internal locus of control, and general self-efficacy; besides, socio-demographic factors such as age, birth order in the family, parent's education, parent's occupation, and the semesters already attended at university. The instrument used is the Personal Growth Initiative Scale, the Life Orientation Test-Revised (LOT-R) to measure optimism, the Internal Locus of Control scale, and the New General Self-Efficacy Scale (NGSE). Through hierarchical regression analysis, the research findings show that general self-efficacy is the strongest predictor of personal growth initiatives, followed by locus of control and optimism. In addition, the socio-demographic data that consistently shows the role of personal growth initiatives is the participants' attended semesters with a negative orientation. The participants' decreasing motivation likely caused the finding due to the increasing number of attended semesters.